Dinamika Perdagangan dan Pertumbuhan Ekonomi Bangka Belitung di Pelabuhan Muntok pada Zaman Belanda ( 1935-1940);Studi Kasus Kota Muntok di Pelabuhan Tanjung Kalian - Saputri, Anggraini; Susanti, L R Retno (Riwayat: Educational Journal of History and Humanities, 2025)
This paper examines trade and economic growth in Muntok, located in the Bangka Belitung Islands, during the Dutch colonial era from 1935 to 1940. The region held a strategic position in international trade routes due to its rich mineral resources, particularly tin, and white pepper. The Port of Tanjung Kalian in Muntok served as a central hub for the export and import of goods, contributing significantly to regional economic development. Using a historical research method, this study employs heuristic approaches, source criticism, interpretation, and historiography. The findings show that colonial infrastructure developmentincluding the port, warehouses, lighthouses, and administrative officeswas aimed at supporting the extraction and export of tin and other commodities, ultimately reinforcing Dutch colonial control. These infrastructures also triggered social and economic changes in the local community. Although locals were involved in the mining and trade sectors, their roles were limited and often under exploitative conditions. The study also highlights the multicultural interactions between local Malays and migrant communities such as the Chinese, Arabs, and Dutch, which shaped the regions social hierarchy and spatial organization. This research emphasizes the significance of colonial infrastructure in facilitating trade and fostering economic growth in Muntok during the colonial period.